2018
DOI: 10.1099/jmm.0.000740
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Candida species in pregnant Chinese women with a molecular beacon method

Abstract: PurposeCandida pathogens are commonly found in women and can cause vulvovaginal candidiasis (VVC), whose infection rate is further increased during pregnancy. We aimed to study the Candida prevalence and strain distribution in pregnant Chinese women with a molecular beacon assay.MethodologyFrom March 2016 to February 2017, a total of 993 pregnant women attending routine antenatal visits at the Beijing Obstetrics and Gynecology Hospital were enrolled. For Candida detection and identification, a unique molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
2
18
0
8
Order By: Relevance
“…However, it was time-consuming (48-72 h) and lacked the reliable sensitivity to discriminate the species by the color of colonies, especially in mixed infection. For example, the differentiation of some C. albicans colonies from dark green colonies of C. dubliniensis, or pale-dark pink/purple C. glabrata colonies from those of species with a similar color were ambiguous, which was in agreement with other studies reporting the same challenge [11,12,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…However, it was time-consuming (48-72 h) and lacked the reliable sensitivity to discriminate the species by the color of colonies, especially in mixed infection. For example, the differentiation of some C. albicans colonies from dark green colonies of C. dubliniensis, or pale-dark pink/purple C. glabrata colonies from those of species with a similar color were ambiguous, which was in agreement with other studies reporting the same challenge [11,12,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…Figure 1 summarizes the distribution of Candida species isolated from vaginal swabs from population-based studies conducted in different countries including our study over the last decade. China, Brazil, Tunis, Kuwait, India, Greece and Turkey have reported that C.albicans remains the most commonly isolated yeast (60%-80%) in women diagnosed with VVC [21][22][23][24][25][26][27]. On the other hand, an increasing trend in the occurrence of NCAC (58%-60%) over time has also been observed in Pakistan and Burkina Faso [28,29].…”
Section: Resultsmentioning
confidence: 98%
“…Kaur et al analyzed Candida strains isolated from six types of clinical samples, and also reported an important predominance of C. albicans [29]. Other studies have analyzed a single type of clinical sample, such as blood [30][31][32][33], urine [21,24], vulvovaginal secretion [34], bronchoalveolar fluid [35], and gastroesophageal tract [36]; however, in all of them the predominant species was C. albicans. Although there are many epidemiological studies that show a trend towards an increase in infections caused by non-albicans Candida species [37], it seems that the C. albicans complex remains the most frequent etiological agent among fungal human infections when considered individually.…”
Section: Discussionmentioning
confidence: 99%